Strategi Dan Pengaruh Promosi Dalam Meningkatkan Penjualan Kacamata Di Optik Jaya Padang - Dolly imam Suryanta; Rina Novalinda (CV. ITTC INDONESIA, 2026)
This scientific paper discusses the strategy and influence of promotion in increasing sales of glasses at Optical Jaya Padang. This KTI aims to find out the promotion strategy and how much influence the promotion has on sales made by Optical Jaya Padang. The type of research that the author uses is descriptive qualitative, where the methods used are observation and interviews. The author conducted interviews with respondents, the respondents who the authors mean are employees of Optical Jaya. After conducting interviews, the authors make observations or observations that aim to make the data that the author can be more complete and real. From the results of the study, it was found that Optik Jaya had carried out various effective promotions including through social media such as Instagram and Facebook as well as through print media. The promotional strategy carried out by Optical Jaya Padang is very influential in increasing sales of glasses. The author suggests that optical jaya further develop the promotions that are currently being carried out so that the promotions carried out can reach a wider community. The author also suggests that Optical Jaya remains consistent in carrying out promotional activities so that the promotions carried out are more effective and can benefit Optical Jaya.